2003
DOI: 10.4049/jimmunol.171.11.5760
|View full text |Cite
|
Sign up to set email alerts
|

Human CD25+ Regulatory T Cells Maintain Immune Tolerance to Nickel in Healthy, Nonallergic Individuals

Abstract: We investigated the capacity of CD25+ T regulatory cells (Treg) to modulate T cell responses to nickel, a common cause of allergic contact dermatitis. CD4+ T cells isolated from the peripheral blood of six healthy, nonallergic individuals showed a limited capacity to proliferate in response to nickel in vitro, but responsiveness was strongly augmented (mean increment ± SD, 240 ± 60%) when cells were depleted of CD25+ Treg. Although CD25+ Treg were anergic to nickel, a small percentage up-regulated membrane CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
124
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 44 publications
(17 reference statements)
9
124
4
8
Order By: Relevance
“…The expression of skin-skewed homing receptors by peripheral blood CD4 ϩ CD25 ϩ T cells was previously reported by the other investigators (4,15); ϳ30% of CD4 ϩ CD25 ϩ T cells expressed CLA and 80% expressed CCR4. These studies, however, did not fractionate CD4 ϩ CD25 ϩ into their functionally distinct components.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The expression of skin-skewed homing receptors by peripheral blood CD4 ϩ CD25 ϩ T cells was previously reported by the other investigators (4,15); ϳ30% of CD4 ϩ CD25 ϩ T cells expressed CLA and 80% expressed CCR4. These studies, however, did not fractionate CD4 ϩ CD25 ϩ into their functionally distinct components.…”
Section: Discussionmentioning
confidence: 77%
“…This combination should allow Treg to enter from blood into secondary lymphoid tissues, suggesting a role for Treg in controlling systemic immunity as central memory T cells (14) at secondary lymphoid organs. In contrast, it has also been reported that unfractionated blood CD4 ϩ CD25 ϩ T cells express variable levels of peripheral tissue-homing receptors such as skin-associated CLA (4,15), CCR4 (16), and gut-associated ␣ 4 ␤ 7 integrin (17). In addition, Iellem et al (15) reported Treg express skin-vs gut-skewed homing receptors, describing that ϳ30% of CD4 ϩ CD25 ϩ T cells express CLA.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…106. 107 The mechanism of suppression induced by these cells is still under debate. In vitro studies suggest the need for cell-cell contact by interaction of the CTLA-4 of the regulatory cell with CD80 and CD86 for inactivation of effector TL.…”
Section: Regulatory T Lymphocytesmentioning
confidence: 99%